2014
DOI: 10.3390/nu6062419
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects of Latent Iron Deficiency on Measures of Cognition: A Pilot Randomised Controlled Trial of Iron Supplementation in Young Women

Abstract: Rates of iron deficiency are high amongst healthy young women. Cognitive impairment occurs secondary to iron deficiency in infants and children, but evaluation of the impact on cognition among young women is inconsistent. The aim was to determine the suitability of the IntegNeuro test battery for assessing cognitive function in iron-deficient and iron-sufficient young women. A pilot double-blinded, placebo-controlled intervention trial was conducted in iron-deficient (serum ferritin ≤ 20 μg/L and haemoglobin >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
3
29
0
4
Order By: Relevance
“…The 2011–2012 Australian Health Survey indicated that 12% of women 16–44 years of age had depleted iron stores (serum ferritin < 15 μg/L [ 1 ]) compared to 1%–2% of Australian men [ 2 ]. Premenopausal women with iron stores at this level are more likely to experience impaired physical performance [ 3 ], and there is some evidence that cognitive ability may also be negatively affected [ 4 , 5 ]. As iron is found in similar food sources to zinc [ 6 , 7 ], inadequate dietary iron and zinc intakes may occur simultaneously [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2011–2012 Australian Health Survey indicated that 12% of women 16–44 years of age had depleted iron stores (serum ferritin < 15 μg/L [ 1 ]) compared to 1%–2% of Australian men [ 2 ]. Premenopausal women with iron stores at this level are more likely to experience impaired physical performance [ 3 ], and there is some evidence that cognitive ability may also be negatively affected [ 4 , 5 ]. As iron is found in similar food sources to zinc [ 6 , 7 ], inadequate dietary iron and zinc intakes may occur simultaneously [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have identified an association between iron status and cognitive performance in young women [ 10 , 34 , 35 ] and an association with academic performance has also been reported [ 36 ]. Empirical studies have reported changes in cognitive performance associated with changes in iron status [ 31 , 34 , 37 , 38 , 39 ]. The cognitive domain of attention was frequently identified [ 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 ], consistent with the finding in the present study that women with IDA had significantly lower attention scores than those with ID.…”
Section: Discussionmentioning
confidence: 99%
“…LID has been observed to be a preceding stage prior to the development of IDA, whereby such progression may be halted by catching the condition early and providing subjects suffering from LID with proper iron supplements [11][12][13], thus, avoiding the derogatory risks of IDA. If left untreated,IDA has been associated with risks of delivering premature babies with low birth weights in pregnant subjects [14].…”
Section: Introductionmentioning
confidence: 99%